Evaluation of the Effectiveness of Wayfinding System Implementation at Uptown Mall Semarang - Aditias Putri, Ninda; Sardjono, Agung Budi (Nature: National Academic Journal of Architecture, 2025)
Navigating complex shopping malls poses significant challenges for visitors, especially when it comes to efficiently locating desired destinations. An ineffective wayfinding system can lead to disorientation and confusion, thereby diminishing the overall user experience. As a multi-functional shopping mall, Uptown Mall Semarang requires a comprehensive evaluation of its existing wayfinding system to facilitate seamless navigation for visitors. On the other hand, this study aims to analyse various wayfinding elements, including architectural design, signage, and sensory information, to assess their effectiveness in aiding visitors’ spatial orientation. The objective of this research is to evaluate the impact of wayfinding system on visitor navigation by examining five basic wayfinding elements: districts, paths, edges, nodes, and landmarks, as well as the role of signage in improving wayfinding efficiency in Uptown Mall Semarang. This research employs qualitative methods, using direct observation supplemented by documentation and interviews with visitors for data collection. The evaluation framework incorporates data triangulation, juxtaposing findings from interviews, observations, and literature on wayfinding architecture and signage that influence the wayfinding process at Uptown Mall. Preliminary findings indicate that Uptown Mall has several wayfinding elements and complementary signage. Overall, these components function effectively to assist visitors in navigating the mall. Nevertheless, challenges remain, particularly with regard to multiple entrances and intersections and the legibility of signage. As a result, there is an urgent need for optimization, which should include a blend of clear signage, intuitive floor design, and enhanced landmark visibility.